Analysis and comparison of different approaches to implementing a network-based parallel data processing algorithm - Skliarova, Iouliia (2022)
It is well known that network-based parallel data processing algorithms are well suited to implementation in reconfigurable hardware recurring to either Field-Programmable Gate Arrays (FPGA) or Programmable Systems-on-Chip (PSoC). The intrinsic parallelism of these devices makes it possible to execute several data-independent network operations in parallel. However, the approaches to designing the respective systems vary significantly with the experience and background of the engineer in charge. In this paper, we analyze and compare the pros and cons of using an embedded processor, high-level synthesis methods, and register-transfer low-level design in terms of design effort, performance, and power consumption for implementing a parallel algorithm to find the two smallest values in a dataset. This problem is easy to formulate, has a number of practical applications (for instance, in low-density parity check decoders), and is very well suited to parallel implementation based on comparator networks.